2021
DOI: 10.1111/tbed.14355
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of atypical porcine pestivirus in the testicles of naturally infected, congenital tremor affected piglets

Abstract: Atypical porcine pestivirus (APPV) belongs to the genus Pestivirus within the family Flaviviridae. Recently, APPV has been identified as the causative agent of congenital tremor (CT) type AII. The disease is a neurological disorder that affects newborn piglets and is characterized by generalized trembling of the animals and often splay legs. CT is well known worldwide, and the virus seems to be highly prevalent in major swine producing areas. However, little is known about the epidemiology of the infection, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The viral distribution was similar in 2-day-old piglets with signs of CT type A-II and in clinically recovered boars (Buckley et al 2021). The other study investigated the testes of new-born piglets with signs of CT type A-II (Dénes et al 2021). This study detected APPV within the walls of medium-sized arteries, the testicular interstitium, and fusiform cells around the primitive, non-functional seminiferous tubules (Dénes et al 2021).…”
Section: Detection Of Appv In Tissuementioning
confidence: 79%
See 2 more Smart Citations
“…The viral distribution was similar in 2-day-old piglets with signs of CT type A-II and in clinically recovered boars (Buckley et al 2021). The other study investigated the testes of new-born piglets with signs of CT type A-II (Dénes et al 2021). This study detected APPV within the walls of medium-sized arteries, the testicular interstitium, and fusiform cells around the primitive, non-functional seminiferous tubules (Dénes et al 2021).…”
Section: Detection Of Appv In Tissuementioning
confidence: 79%
“…Thus, the results from these two studies are not congruent. In the study by Buckley et al (2021), APPV was detected beyond the Sertoli cell barrier (blood-testis barrier), whereas Dénes et al (2021) reported that no virus was detected in cells beyond the blood-testis barrier of the new-born piglets.…”
Section: Detection Of Appv In Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Using processing fluids to monitor the presence of different infectious agents has a lot of well-known advantages and it has been used for the detection of various porcine pathogens, including PRRSV [42], APPV [43] or Mycoplasma hyopneumoniae [44]. A retrospective study from the USA commonly detected PCV3 in clinical cases of PDNS and PMWS and tissue samples from aborted fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…The participation in the sampling campaign was voluntary of all farms regardless of their health status, and no significant clinical disease was reported in the herds during the sampling period. On most farms, according to the protocol, 100 blood samples were drawn from animals of different age groups, 5 pen-based oral fluid samples were collected from weaned pigs (8-12 weeks of age; WOA), and 5 samples from fatteners (18-20 WOA) [14]. More details of the sampling protocol can be found in the study of Igriczi et al [15].…”
Section: Methodsmentioning
confidence: 99%